THE IMPLEMENTATION OF SCIENTIFIC APPROACH TO THE PJOK LEARNING AT THE TARGET SECONDARY SCHOOLS OF THE 2013 CURRICULUM IN NORTH SUMATRA - Irfan, M.; Sugiharto, Sugiharto; Hidayah, Taufiq (The Journal of Educational Development, 2017)
The Scientific approach is among the ways to achieve the goals of the 2013 Curriculum (K13). The short period of time for the teacher training and others are assumed to be the cause of the gradual implementation of K13. In line with this, the Government intends to reorganize the way in which the K13 is implemented. The Government has assigned several schools to be analyzed as the target schools to improve. This study intends to contribute to it by analyzing the pattern of scientific `approach implemented by the teachers in teaching their students so that the teachersâ performance in conducting teaching-learning processes can be managed in accordance with the K13. This research aimed to determine the level of perceived gaps on the way the teachers implemented the scientific approach in physical education, sports, and health (PJOK) learning at the target schools of the K13 in the province of North Sumatra. The data were analyzed in order to obtain an overview and improvement solutions in managing scientific approach to PJOK learning that foster a positive impact on the aspects of growth and the studentsâ development in line with the expectation of the K13. The research method applied in this study refers to the discrepancy approach developed by Malcolm Provus. This approach was meant to find out gaps in the program. The research was carried out by inventorying standard references in implementing the pattern of the scientific approach. The results of inventorying become the standard criteria of data collection and analysis in this study. The analysis revealed that the PJOK teachers have not completely implemented the scientific approach. The implementation patterns were neither consistent nor appropriate.  The teachers understanding about the demand of the scientific approach pattern management of the K13 was inadequate.